Sistem Pakar Penyakit Sapi Menggunakan Rule Based Reasoning dengan Forward Chaining - Alfian, Muhammad; Aprianti, Winda; Rhomadhona, Herfia; Permadi, Jaka (Fakultas Teknik dan Teknologi Informasi, Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Tanah Laut Regency is a district in South Kalimantan known as a livestock farming hub, particularly for beef cattle farming. The beef cattle population in this regency reached 88,420 heads in 2023. This large number of beef cattle requires greater attention from the local government. The Livestock and Animal Health Office of Tanah Laut Regency has Field Extension Officers (PPL) stationed in every village to monitor and inspect the condition of beef cattle owned by farmers. The issue is that monitoring results are still recorded manually, and farmers lack sufficient knowledge about beef cattle diseases. As a result, diseases are often not detected early, leading to severe conditions and even death. An expert system with forward chaining reasoning is necessary to reduce farmers' dependence on PPL due to their limited knowledge of beef cattle diseases. The expert system was developed based on a knowledge base derived from literature studies and interviews with an expert (one of the PPL officers). Data collected includes 21 diseases and 62 symptoms. The database used for the system consists of six tables. The system's functionality was tested using Blackbox Testing, and all functionalities performed well. The accuracy of the expert system was tested using 10 test data samples, achieving an accuracy rate of 90%.